Feasibility of Cancer Immunotherapy with WT1 Peptide Vaccination for Solid and Hematological Malignancies in Children. Issue 2 (15th October 2015) - Sawada, Akihisa; Inoue, Masami; Kondo, Osamu; Yamada‐Nakata, Kayo; Ishihara, Takashi; Kuwae, Yuko; Nishikawa, Masanori; Ammori, Yasuhiro; Tsuboi, Akihiro; Oji, Yusuke; Koyama‐Sato, Maho; Oka, Yoshihiro; et al.
Abstract : Background: Advances in cancer immunotherapy in the pediatric field are needed in order to improve the prognosis of children with malignancies. We conducted a prospective phase I/II study of WT1 peptide vaccination for children with relapsed or refractory malignancies. Methods: The main eligibility criteria were affected tissues or leukemic cells expressing the WT1 gene, and patients (and donors for allogeneic hematopoietic stem cell transplantation) having HLA‐A*24:02. Vaccination using the WT1 peptide (CYTWNQMNL), which was modified for higher affinity to this HLA‐type molecule with the adjuvant Montanide ISA51, was performed weekly 12 times. Results: Twenty‐six patients were enrolled and 13 (50.0%) completed the vaccination 12 times. Evidence for the induction of WT1‐specific cytotoxic T‐lymphocyte (CTL) responses without severe systemic side effects was obtained. Two out of 12 patients with bulky disease exhibited a transient clinical effect (one mixed response and one stable disease), three out of six patients with minimal residual disease achieved transient molecular remission, and five out of eight patients without a detectable level of the molecular marker, but with a high risk of relapse, had the best outcome of long‐term continuous complete remission. Conclusions: WT1 vaccination is a safe immunotherapy and induced WT1‐specific CTL responses in children; however, as a single agent, vaccination only provided patients in remission, but with a high risk of relapse, with "long‐term benefits" in the context of its use for relapse prevention. WT1 peptide‐based treatments in combination with other modalities, such as anti‐tumor drugs or immunomodulating agents, need to be planned.